2023
DOI: 10.13057/biodiv/d240712
|View full text |Cite
|
Sign up to set email alerts
|

Morphological parameters, heritability, yield component correlation, and multivariate analysis to determine secondary characters in selecting hybrid maize

NUR FADHLI,
MUH FARID,
MUHAMMAD AZRAI
et al.

Abstract: Abstract. Fadhli N, Farid M, Azrai M, Nur A, Effendi R, Priyanto SB, Nasruddin AD, Novianti F. 2023. Morphological parameters, heritability, yield component correlation, and multivariate analysis to determine secondary characters in selecting hybrid maize. Biodiversitas 24: 3750-3757. Direct selection for grain yield traits in maize (Zea mays L.) is often inefficient under specific conditions, necessitating the accurate determination of secondary traits to facilitate implementation and enhance selection precis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…[23] found that cob length was positively and significantly correlated (0.43 ** ) to maize seed yield per plant. [24] also added that maize cob length was positively correlated (0.72 ** ) to the number of seeds.…”
Section: Correlation Valuementioning
confidence: 99%
“…[23] found that cob length was positively and significantly correlated (0.43 ** ) to maize seed yield per plant. [24] also added that maize cob length was positively correlated (0.72 ** ) to the number of seeds.…”
Section: Correlation Valuementioning
confidence: 99%
“…Path analysis is a statistical technique employed to investigate the direct and indirect impacts of one trait on another using multivariate methods and offers dependable information about the role of traits in improving yield. This method is valuable for determining the best secondary traits and is considered a more complex technique than regression analysis, particularly for assessing the direct effects of traits [26]. The results of the path analysis of selection traits for yield in acidic soil are presented in table 4.…”
Section: Correlation and Path Analysis Of Selection Traitsmentioning
confidence: 99%
“…To effectively select multi-parameter methods, multivariate analysis is recommended as a powerful tool to simplify relationships between variables [35]. This approach is instrumental in evaluating multiple characteristics simultaneously [36]. Therefore, in this study, the employed multivariate analysis aims to identify useful traits for efficient and effective fertilizer dosing.…”
Section: Introductionmentioning
confidence: 99%